Politik Hukum di Indonesia: Dinamika dan Implementasinya dalam Sistem Hukum Nasional - Dian Amelia Sari; Nur Resky Aulia; Novi Arliati; Kurniati Kurniati (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study discusses the dynamics of Islamic legal politics in Indonesia and its implementation within the national legal system. The research is motivated by the growing role of Islamic law in the process of legislation and constitutional life in Indonesia as a pluralistic society. The study aims to analyze the forms of dynamics in Islamic legal politics, the opportunities and challenges faced, and their impacts on the national legal system. The research employs a normative legal method using statutory and conceptual approaches through the analysis of various literature, regulations, and legal scholars’ perspectives. The findings indicate that the dynamics of Islamic legal politics are reflected in the accommodation of sharia values within national regulations, the development of religious courts, and the growth of the sharia economic sector. However, its implementation also faces challenges related to legal pluralism, ideological debates, and human rights issues. This study concludes that Islamic legal politics has a significant contribution to the development of the national legal system as long as it is implemented in a moderate, inclusive, and constitutional manner in accordance with Indonesian principles.